ON LANGUAGE ACQUISITION: KEY FACTORS IN ACQUIRING FOREIGN LANGUAGE NATURALLY - Muhammad Taufik Hidayat (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
Language Acquisition has always been the purpose for every language learning process. Many researchers and experts have involved in the search for the holy grail of finding the most appropriate method, technique or strategies for teaching English. Instead of attempting to apply what so called the most appropriate method for language learning, learning from â€œsuccessfulâ€ learners seems to provide a shortcut in providing the explanation for this matter. Hence, this study was intended to discover the foreign language acquisitions process by conducting retrospective analysis. To this end, ex-post facto study was chosen as the research design. There are five participants purposively chosen as the data source for this study. They were chosen due to their language competence and performance deemed appropriate in providing information needed in this ex post facto study. The main instruments primarily used in this study were interviews and document analysis. Document analysis was used to confirm the actual language competence of the participants deemed as successful English learners. The interview, on the other hand, was used to explore the contributing or determinant factors during their language acquisition process. The result revealed that language exposure, motivation, attitude and socioeconomic status are prominent in affecting the foreign language acquisitions. In addition to these factors, native-level input was also acknowledged influential to the success of the participantsâ€™ language acquisition. In addition, this finding was expected to provide more insight in understanding foreign language acquisition in EFL context and it will eventually contribute to improve the foreign language practice in EFL context